The Impact of COVID-19 on Tourism: A Case Study of Lumbini, Nepal - Kunwar, Bhim Bahadur (The Gaze: Journal of Tourism and Hospitality, 2021)
This research aims to discover and present the impacts of COVID-19 in tourism in the context of Lumbini and its premises. As COVID-19 spread globally, it has created many challenges in health and security, daily lives, the national economy, and the global tourism industry. The COVID-19 outbreak has been considered as the most challenging tragedy that occurred in the world after the 2nd world war. The World Health Organization (WHO) had listed Nepal also as a country with a high-risk zone of COVID-19.The travel restriction and nationwide lock-down implemented by many countries including Nepal have resulted in a stranded traveler’s movement. As the consequences ticket reservation, flight services, transportation, hotel, and restaurants were closed and several job losses were registered in the tourism sector. The negative effects like fear, threat, frustration, and losing the confidence of tourism entrepreneurs appeared. This has brought changes in the tourists’ behavior and their motivation to travel for the next few years. In Lumbini businesses like lodges, hotels, restaurants, and travel offices were also severely affected by the pandemic. Thus, the tourism sector has been facing serious threats due to the prolonged lockdown and closing of tourism activities than the terror of COVID-19 itself.